2006
DOI: 10.1159/000090947
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine-Induced Endothelin-1 Release Is Dependent on Hyperglycaemia and Reactive Oxygen Species Production in Bovine Aortic Endothelial Cells

Abstract: Background: Elevated plasma homocysteine (Hcy) is a risk factor for coronary disease. The objective of this study was to investigate whether Hcy either alone or in high glucose conditions induces endothelin-1 (ET-1) synthesis via the production of reactive oxygen species (ROS). Methods: Bovine aortic endothelial cells were grown in high (25 mmol/l) and low (5 mmol/l) glucose medium. Results: In high glucose, Hcy caused a time-dependent increase in ET-1 release, which was greatest with 50 µmol/l Hcy at 24 h (p … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 76 publications
1
20
0
1
Order By: Relevance
“…Replacement of this cysteine residue with serine prevents the modification and, therefore, makes the protein insensitive to the redox regulation. The existence of this mechanism of control may shed light on previous observations of upregulated ET-1 expression upon exposure of endothelial cells to oxidants (46,51). The regulation of the mRNA-destabilizing capacity of GAPDH by oxidative and nitrosative stress presents an extremely interesting scenario regarding the endothelium, where the contribution of NO and oxidants to the vascular pathophysiology is important (24,48).…”
Section: Discussionmentioning
confidence: 80%
“…Replacement of this cysteine residue with serine prevents the modification and, therefore, makes the protein insensitive to the redox regulation. The existence of this mechanism of control may shed light on previous observations of upregulated ET-1 expression upon exposure of endothelial cells to oxidants (46,51). The regulation of the mRNA-destabilizing capacity of GAPDH by oxidative and nitrosative stress presents an extremely interesting scenario regarding the endothelium, where the contribution of NO and oxidants to the vascular pathophysiology is important (24,48).…”
Section: Discussionmentioning
confidence: 80%
“…However, in endothelial cells, there is only indirect evidence that ET-1 can increase mitochondrial ROS. For example, the combined metabolic burden of homocysteine and high glucose stimulates ET-1 synthesis in bovine aortic endothelial cells via a mechanism dependent on the production of mitochondrial ROS (29). Furthermore, in human aortic endothelial cells, uncoupling protein 2 overexpression decreases ET-1 mRNA expression and prevents the disruption of the mitochondrial membrane potential induced by lysophophatidylcholine (30).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Tyagi et al [68] have shown a positive relationship between cellular mitochondrial oxidative stress and systemic hypertension in hHcys. Sethi et al [76] also reported that a combined metabolic burden of Hcys and high glucose stimulates ET-1 synthesis in endothelial cells via a mitochondrial ROS-dependent mechanism and thereby results in cell dysfunction. Given the similarity of pathological changes at the cellular or molecular levels in glomerular injury and arterial damages, mitochondria-derived ROS may also be importantly involved in the initiation and progression of Hcys-induced glomerular sclerosis.…”
Section: Local Oxidative Stressmentioning
confidence: 99%